Correlates and outcomes associated with sexting among justice involved youth: The role of developmental adversity, emotional disinhibitions, relationship context, and dating violence. (November 2018) - Yoder, Jamie; Hansen, Jesse; Precht, Madison
Abstract: To date, the majority of the research on sexting is descriptive; yet, there is an emergence of scholarship on the correlates to and consequences of sexting. While etiological underpinnings have yet to be fully conceptualized, The Developmental Vulnerability Theory may be used to explain sexting behavior and other non-sexual violent behavior including dating violence. The DVT posits that early victimization results in vulnerabilities, disinhibiting influences, and conditioning experiences can manifest over time to create propensities for sexual and non-sexual violence. As technological advancements have been made, there are new disinhibiting factors to consider, and, cell phones equipped with the ability to send and receive messages not only provide opportunities for youth to socially interact in a disinhibited manner, but they may exacerbate existing emotional disinhibition for youth with adverse relational histories and resulting vulnerable emotional states. This may contribute to emotional disinhibitions that drive sexting behaviors. Using data on adjudicated youth in a western state ( N  = 200), this study examined the prevalence rates of sexting, tested associations between developmental adversities, emotional motivations for sexting, and relationship context; and determined the relationship between sexting and dating violence perpetration. Results revealed a range of high and low sexting rates (21% to 73.5%). Early life domestic adversity and physical abuse was associated with more frequent sexting outside of dating relationships (friends and acquaintances). Emotional motivations for sexting was associated more frequent sexting outside of dating relationships. In the final multivariate model, emotional motivations and sexting friends and acquaintances was associated with dating violence. Treatment, policy, and research implications are discussed.